Privileging Narratives: Singing, the Polish Tatras, and Canada - Wrazen, Louise (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
The traditional singing of Górale from the Tatra mountain region of Podhale favours a single phrase of melody and two lines of text. The narrative significance of this singing is traced from homeland to diaspora: collectively, these songs constitute a regional narrative that in Poland provided the framework for personal expressions constructed spontaneously in performance and embedded in social discourse; in Canada, the individual story is subsumed in favour of a collective narrative that locates a meaningful space between these two worlds. Ultimately, the centrality of music in the experience and deliberate expression of difference within an evolving multicultural, transnational, globalized reality is reinforced.